Child and adolescent psychiatry training in Nepal: early career psychiatrists' perspective - Utkarsh Karki; Yugesh Rai; Gunjan Dhonju; Eesha Sharma; Preeti Jacob; John Vijay Sagar Kommu; Shekhar P. Seshadri (BMC, 2020)
Abstract Background Nepal is a developing low-income country in Southeast Asia. There is a huge burden of child and adolescent mental health (CAMH) in Nepal which has a population of around 29 million and 40-50% of the population comprises of children and adolescents. Child and Adolescent Psychiatry (CAP) has not been formally recognized as a subspecialty in Nepal and there is no standardized curriculum for CAP training. The objectives of the survey were to identify the current status of training, shortfalls and to explore the training experiences of early career psychiatrists (ECPs) in Nepal. Methods The participants were ECPs in Nepal. An online questionnaire was created consisting of 20 questions including 3 questions requiring an answer indicating a level of agreement scored on a ten-point scale. Questionnaire using google form was e-mailed with the uniform resource locator (URL). Respondents anonymously answered the questions. The survey was open from 01/01/2019 to 01/04/2019. Results Response rate was 83.69%. Around 42% (n = 32) were trainees in Doctor of Medicine (MD) Psychiatry and 58% (n = 45) of respondents had completed their MD Psychiatry. More than half of the ECPs had not received formal training specific to CAP. Seventy percent (n = 54) ECPs reported that their current workplace did not have a specific unit to address psychological problems in children and adolescents. However, 62% (n = 48) of ECPs came across 10 CAP cases per week. On a ten-point scale, mean score of ECPs confidence in diagnosing, management and overall confidence in CAP cases were 5.18 ± 1.56, 4.58 ± 1.59 and 4.67 ± 1.62 respectively. Fifty-four percent (n = 42) of respondents rated their training as limited and 74% (n = 57) of them wanted additional training in CAP. Psychological intervention, psychotherapy and a fellowship course were the additional training most of the ECPs wanted to receive. Conclusion Despite significant exposure to CAP patients in daily practice, ECPs self-evaluated their training as inadequate and there is no standardized CAP training program in Nepal for ECPs. The desire of ECPs to receive additional training in CAP is highly encouraging and positive. We advocate for the development and incorporation of CAP training in current psychiatry training to fulfill these unmet training needs in Nepal.